具有基于MRI基导电率测量结果的在头部上的电极位置优化的TTFIELD治疗 (2025)
当电极用于在解剖体积内的目标组织中施加电场(例如，应用TTField以治疗肿瘤)时，电极的位置可以通过在解剖体积中获得电导率测量结果并且直接根据所获得的电导率或电阻率测量结果生成导电率的3D图来优化，而不将解剖体积分成组织类型。在解剖体积内识别目标组织的位置，并且基于电导率的3D图和目标组织的位置确定用于电极的位置。 A method of optimizing positions of a plurality of electrodes for placement on a subject's body, the method comprising the steps of: generating a 3D map of electrical conductivity or resistivity of an anatomic volume directly from electrical conductivity or resistivity measurements, without segmenting the anatomic volume into tissue types; identifying a location of target tissue within the generated 3D map of electrical conductivity or resistivity; and determining positions for placement of the electrodes based on the generated 3D map of electrical conductivity or resistivity and the identified location of the target tissue.